Prosthetic restoration of the forefoot lever after Chopart amputation and its consequences onto the limb during gait - Kaib, Thomas; Block, Julia; Heitzmann, Daniel; Putz, Cornelia; Alimusaj, Merkur; Wolf, Sebastian Immanuel (Gait & posture, 2019)
Background - In subjects with Chopart amputation the foot lever is clearly diminished. Usually high or low profile prostheses are routinely utilized to re-establish the lost forefoot lever. - Research question - The aim of this study was to investigate to what extent the proposed prostheses were able to replace the forefoot lever in chopart-amputees. - Methods - An instrumented 3D gait analysis, including plantar and socket pressure measurements, was performed in thirteen subjects with Chopart amputation using a clamshell and/or a Bellmann prosthesis including an ankle foot orthosis during level ground walking. - Results - The largest range of motion (p<0.05) in the ankle joint was seen for the Bellmann prosthesis (32±3°) followed by the Bellmann prosthesis with ankle-foot orthosis (22±6°) whereas in the clamshell prosthesis (10±4°) almost no ankle motion was seen. Conversely, the highest ankle joint moment (p<0.05) was seen for the clamshell prosthesis (1.04±0.24Nm/kg) followed by the Bellmann prosthesis with ankle-foot orthosis (0.66±0.14Nm/kg) and, finally, the Bellmann (0.37±0.11Nm/kg) alone offering the lowest joint moment. - Conclusion - High-profile prostheses with ventral shell are more suitable to reacquire the lost forefoot lever after Chopart amputation. However, the issue of restricted range of motion in the ankle joint with the clamshell prosthesis needs to be addressed.